The effect of sovereign debt on Capital inflows to Zambia - Lunda, Mutinta M (Research of GSB, 2019)
Over the last 10 years, many Sub Saharan countries have tapped into the international market to issue sovereign bonds to boost economic growth and attract additional foreign direct investments. Funds obtained have been used for large infrastructure projects and easing of balance of payments to name but a few. Zambia between the years 2011-2015 borrowed heavily on the international market totaling just around US$ 4 billion in Eurobonds to drive jobs and fill gaps in essential infrastructure in the energy and health sectors. Financing of large infrastructure projects had been a main topic for governments in Zambia and the local market did not have the capacity. Upon receiving its sovereign rating, Zambia saw the international bond market as an avenue. Accessing of the international bond market for African nations had grown noticeably due to eased financial conditions on the global market. Thirteen countries had tapped into the international markets by the end of March 2014 for various reasons which mostly included economic growth. Many market players have kept a close watch on the rising debt levels particularly in sub Saharan Africa to ensure that it does not reach levels similarl to those of HIPC. In 2005, Zambia’s debt stood at US$ 5.4 billion which was unsustainable and represented 74% of Zambia’s GDP and approximately 208% of export earnings (IHS Global Insights, 2014). Having their debt relieved by the IMF and World Bank in 2006 reduced their debt burden to around 25% of GDP. Following that, the Zambian government in 2012 issued its first Eurobond and borrowed excessively in the years to follow that the debt to GDP ratio reached almost 40%. Coupled with that, Zambia experienced a reduced price in its major export commodity copper and a tumbling exchange rate. It has become clear that access to international capital markets and high levels of public debt has made the Zambian economy more susceptible to shocks and leaves them vulnerable and does not achieve desired goals of growth and does not encourage foreign direct investment through capital inflows. This paper examines the effect of capital inflows to Zambia as a result of rising public debt levels. It focuses on the impact of Zambia’s sovereign debt on capital inflows for a period of 15 years (between 2000 and 2015). The findings suggest an inverse relationship between sovereign debt and capital inflows. The findings also suggest a positive relationship between a countries international reserves and capital inflows. These relationships were found to be significant which suggests that external debt could influence capital inflows to Zambia.